Contrasting vegetation change (1974–2015) in hedgerows and forests in an intensively used agricultural landscape. Issue 2 (11th March 2019) - Van Den Berge, Sanne; Tessens, Sam; Baeten, Lander; Vanderschaeve, Cecile; Verheyen, Kris
Abstract: Questions: How did hedgerows and forests change in area between 1974 and 2015 and did hedgerows still show the same vegetation composition in 2015? To what degree did the vegetation change in hedgerows and how do these changes compare to changes in forests? What is the nature of the species that changed and, from these, can we make general inferences about possible drivers of change? Location: The countryside in the municipality of Turnhout, province of Antwerp, northern Belgium. Methods: Through a resurvey of 54 and 20 quasi‐permanent plots in hedgerows and forests, respectively, we investigated shifts in the herb layer over the period 1974–2015. The plot‐level mean Ellenberg Indicator Values (EIVs) were calculated and soil samples were taken in 2015. We compared diversity statistics and used used Generalized Linear Mixed‐Effects Models (GLMMs) to detect trends in species richness (SR) and EIVs. Via a non‐metric multidimensional scaling (NMDS) ordination based on the Sørensen dissimilarity, we compared shifts at the community level. Results: Our study shows severe, but opposite changes in SR in forests and hedgerows. In forests, SR declined and a homogenization occurred. The shifts in EIVs indicate that forest vegetation evolved to more shade‐tolerant and nutrient‐demanding species, likely due to eutrophication combined with natural forest succession. In hedgerows, SR significantly increased. The species pool became more diverse and more heterogeneous. Changes in EIVs suggest a change towards more light‐demanding species, possibly caused by fragmentation of the network, and towards species indicative for nutrient‐rich habitats, benefiting from eutrophication. Conclusions: In general, SR in hedgerows is higher than in forests in our studied region, being a suitable habitat for a wide range of plant species in the countryside. However, the loss of almost 30% of the hedgerow habitat in 41 years confronts us with the challenge of protecting the hedgerow remnants, in the interest of agro‐biodiversity. Abstract : Through a resurvey in hedgerows and forests in northern Belgium, we investigated the shifts in the herb layer (1974–2015). Our study shows severe, but opposite changes in species richness (SR) in forests and hedgerows. In hedgerows, SR significantly increased and the species pool became more heterogeneous, whereas in forests SR declined and homogenization occurred.